The Brasilia Rules and the rights of the family, children, and adolescents. Access to justice in cases of international return of children and adolescents and visitation or international contact - Tagle de Ferreyra, Graciela (2021)
Access to justice as a fundamental human right must be guaranteed at all stages of the process and also in the execution of the sentence. This approach is evident in the current challenges in the jurisdictional function. International child return cases must be resolved within a reasonable period of six weeks. To this end, the procedure must be regulated and judges must have the necessary means to make appropriate decisions. Access to justice in these cases involves three vulnerable groups: children because of their age, those who litigate at a distance, and women because of their gender. In this article, we will analyze each of them considering the challenges of our time.